The Janes - Luna, Louisa (An Alice Vega novel, 2020)
"On the outskirts of San Diego, the bodies of two young women are discovered. They have no names, no IDs, and no family looking for them. Fearing the possibility of a human trafficking ring, the police and FBI reach out to Alice Vega, a private investigator known for finding the missing, for help in finding out who the Janes were--and finding the others who are missing. Alice Vega is a powerful woman whose determination is matched only by her intellect, and, along with her partner Cap, she will stop at nothing to find the Janes before it is too late."--